THE ROLE OF THE FAMILY IN PREVENTING ADOLESCENTS' RISK-RELATED ONLINE GAMBLING (Universal International Scientific Journal, 2026)
The role of the family in preventing the risk-taking tendency of these adolescents to engage in online gambling is highlighted. The importance of the family in the formation and prevention of addiction to online gambling during adolescence is also explained.
Keywords: online gambling, risk-taking behavior, family, adolescent psychology, addiction, cognitive disorders, emotional regulation, social isolation, psychological and cognitive development, comorbidity.